Uremia‐Induced Gut Barrier Defect in 5/6 Nephrectomized Mice Is Worsened by Candida Administration through a Synergy of Uremic Toxin, Lipopolysaccharide, and (1à3)‐β‐D‐ Glucan, but Is Attenuated by Lacticaseibacillus rhamnosus L34 - Somkanya Tungsanga (2022)
A chronic kidney disease (CKD) causes uremic toxin accumulation and gut dysbiosis, which further induces gut leakage and worsening CKD. Lipopolysaccharide (LPS) of Gram‐negative bacteria and (1à3)‐β‐D‐glucan (BG) of fungi are the two most abundant gut microbial molecules. Due to limited data on the impact of intestinal fungi in CKD mouse models, the influences of gut fungi and Lacticaseibacillus rhamnosus L34 (L34) on CKD were investigated using oral C. albicans-administered 5/6 nephrectomy (5/6Nx) mice. At 16 weeks post‐5/6Nx, Candida‐5/6Nx mice demonstrated an increase in proteinuria, serum BG, serum cytokines (tumor necrotic factor‐α; TNF‐α and interleukin‐6), alanine transaminase (ALT), and level of fecal dysbiosis (Proteobacteria on fecal microbiome) when compared to non‐Candida‐5/6Nx. However, serum creatinine, renal fibrosis, or gut barrier defect (FITC‐dextran assay and endotoxemia) remained comparable between Candida‐ versus non‐Candida‐5/6Nx. The probiotics L34 attenuated several parameters in Candida‐5/6Nx mice, including fecal dysbiosis (Proteobacteria and Bacteroides), gut leakage (fluorescein isothiocyanate (FITC)‐dextran), gut‐derived uremic toxin (trimethylamine‐N‐oxide; TMAO) and indoxyl sulfate; IS), cytokines, and ALT. In vitro, IS combined with LPS with or without BG enhanced the injury on Caco‐2 enterocytes (transepithelial electrical resistance and FITC‐dextran permeability) and bone marrow‐derived macrophages (supernatant cytokines (TNF‐α and interleukin‐1 β; IL‐1β) and inflammatory genes (TNF‐α, IL‐1β, aryl hydrocarbon receptor, and nuclear factor‐κB)), compared with non‐IS activation. These injuries were attenuated by the probiotics condition media. In conclusion, Candida administration worsens kidney damage in 5/6Nx mice through systemic inflammation, partly from gut dysbiosis‐induced uremic toxins, which were attenuated by the probiotics. The additive effects on cell injury from uremic toxin (IS) and microbial molecules (LPS and BG) on enterocytes and macrophages might be an important underlying mechanism.